Consistency between Schedule for Oral-Motor Assessment - Persian and Fluoroscopic Barium Swallow Study - Manijeh Zarei Mahmood Abadi; Fariba Yadegari; Mehrzad Mehdizade; Lida Sharifi-Rad; Enayatollah Bakhsh (Shiraz University of Medical Sciences, 2023)
Background: A swallowing disorder is one of the most common problems in the pediatric population. Schedule for Oral-Motor Assessment (SOMA) has become one of the best methods for the assessment of swallowing disorders in the pediatric population. In this study, we evaluated the sensitivity, specificity, and consistency of SOMA by fluoroscopic barium swallow study.Methods: This is a descriptive-analytical study. SOMA was assessed on 52 children with swallowing problems. The children were 6 to 48 months and had been referred for a fluoroscopic barium swallow. We analyzed sensitivity; specificity, positive predictive value, and negative predictive value of SOMA, with the fluoroscopic barium swallow as the gold standard. For the evaluation of the correlations among variables, Cronbach's coefficient alpha was calculated.Results: In this study 6 parts of SOMA had 0-25% sensitivity, 90-97% specificity, 0-66% positive predictive value, 84-87% negative predictive value, 78-86% compatibility percent and 0.06-0.17 kappa value. Internal consistency was 0.93 using Cronbach's coefficient alpha.Conclusion: The results of this study suggest that SOMA is valid for the evaluating of swallowing disorders.  It can use as a screening test and as a complementary method to fluoroscopic barium swallow.